Flavivirus NS1 Triggers Tissue-Specific Disassembly of Intercellular Junctions Leading to Barrier Dysfunction and Vascular Leak in a GSK-3β-Dependent Manner - Henry Puerta-Guardo; Scott B. Biering; Francielle Tramontini Gomes de Sousa; Jeffrey Shu; Dustin R. Glasner; Jeffrey Li; Sophie F. Blanc; P. Robert Beatty; Eva Harris (Pathogens, 2022)
The flavivirus nonstructural protein 1 (NS1) is secreted from infected cells and contributes to endothelial barrier dysfunction and vascular leak in a tissue-dependent manner. This phenomenon occurs in part via disruption of the endothelial glycocalyx layer (EGL) lining the endothelium. Additionally, we and others have shown that soluble DENV NS1 induces disassembly of intercellular junctions (IJCs), a group of cellular proteins critical for maintaining endothelial homeostasis and regulating vascular permeability; however, the specific mechanisms by which NS1 mediates IJC disruption remain unclear. Here, we investigated the relative contribution of five flavivirus NS1 proteins, from dengue (DENV), Zika (ZIKV), West Nile (WNV), Japanese encephalitis (JEV), and yellow fever (YFV) viruses, to the expression and localization of the intercellular junction proteins β-catenin and VE-cadherin in endothelial cells from human umbilical vein and brain tissues. We found that flavivirus NS1 induced the mislocalization of β-catenin and VE-cadherin in a tissue-dependent manner, reflecting flavivirus disease tropism. Mechanistically, we observed that NS1 treatment of cells triggered internalization of VE-cadherin, likely via clathrin-mediated endocytosis, and phosphorylation of β-catenin, part of a canonical IJC remodeling pathway during breakdown of endothelial barriers that activates glycogen synthase kinase-3β (GSK-3β). Supporting this model, we found that a chemical inhibitor of GSK-3β reduced both NS1-induced permeability of human umbilical vein and brain microvascular endothelial cell monolayers in vitro and vascular leakage in a mouse dorsal intradermal model. These findings provide insight into the molecular mechanisms regulating NS1-mediated endothelial dysfunction and identify GSK-3β as a potential therapeutic target for treatment of vascular leakage during severe dengue disease.